Self-Efficacy and Family Support in Female Hospital Employee Turnover Intention - Kadek Julia Praba Dewi; Agus Wahyudi Salasa Gama; I Gusti Ayu Imbayani (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines turnover intention among female hospital employees by explaining how work-family conflict and job stress influence the intention to leave through self-efficacy and family organizational support. Methodology: This study used a quantitative survey design at Rumah Sakit Umum Daerah (RSUD) Wangaya Denpasar City, Bali, Indonesia. The population comprised 729 female employees, and 259 respondents were selected using Slovin’s formula. Data were collected using structured questionnaires, supported by interviews and documentation. The model was analyzed using SmartPLS 3.0 via partial least squares structural equation modeling. Results: Work-family conflict and job stress negatively affected self-efficacy and positively affected turnover intention. Self-efficacy negatively affected turnover intention and partially mediated the effects of work-family conflict and job stress. Family organizational support moderated several paths, although it did not significantly moderate the effect of job stress on turnover intention. Conclusions: Female hospital employees are more likely to consider leaving when role conflict and job stress reduce their confidence in managing work demands. Limitations: The study used cross-sectional data from one public hospital; therefore, causal claims and generalization remain limited. Contributions: This study contributes to human resource management by integrating psychological and organizational mechanisms to explain turnover intention among female healthcare employees.